Advances in Lung Cancer Driver Genes Associated With Brain Metastasis - Kang, Yalin; Jin, Yu; Li, Qianxia; Yuan, Xianglin (Frontiers in Oncology, 2021)
Brain metastases, one of the common complications of lung cancer, is an important cause of death in patients with advanced cancer, despite progress in treatment strategies. Lung cancers with positive driver genes have a higher incidence and risk of brain metastases, suggesting that driver events associated with these genes might be biomarkers to detect and prevent disease progression. Common lung cancer driver genes encode mainly receptor tyrosine kinases (RTKs), which are important internal signal molecules that interact with external signals. RTKs and their downstream signal pathways are crucial for tumor proliferation, invasion, immune microenvironment inhibition and colonization in the brain. In addition, new tumor driver genes, which also encode important molecules in the downstream signaling pathways of RTKs, have been found to be closely related to the brain metastases of lung cancer. In this article, we reviewed the role of lung cancer driver genes in brain metastasis, and summarized the driver-gene associated mechanism of brain metastasis. By understanding the molecular characteristics during brain metastasis, we can better stratify lung cancer patients and alert those at high risk of brain metastasis, which helps to promote individual therapy for lung cancer.